PENGEMBANGAN BAHAN AJAR BERBASIS PROBLEM BASED LEARNING PADA MATERI BILANGAN BULAT - Ahmad Tarmizi; Hidayat, Hidayat (Bajang Institute, 2025)
This research aims to: (1) Reveal teaching materials based on problem based learning on Whole Numbers material, (2) Determine the feasibility of teaching materials based on problem based learning on Whole Numbers material. This research is a type of Research and Development (R&D) research with a 4 D model which includes four steps, namely: defining, designing, developing, disseminating. However, this research is limited to only three stages, namely only the development stage. The subjects of this research are material expert validators, open material experts and learning experts. The instrument used to collect data was a questionnaire. This research produces a product in the form of book teaching materials based on problem based learning on Integer Numbers. Based on the validation results from material experts, teaching materials experts and learning experts, it has been proven that the product has received a good assessment and is very suitable for use